Member of the Editoria Board - Krambia-Kapardis, Maria (My University, 2026)
https://www.emeraldgrouppublishing.com/journal/jaee?distinct_id=%24device%3A19503b920b3688-07378ac593a8de-26011a51-170ef6-19503b920b3688&_ga=2.145820791.2141534767.1739524220-1915126598.1739524220&_gl=1*1o8ql2j*_ga*MTkxNTEyNjU5OC4xNzM5NTI0MjIw*_ga_45RWY1YP1V*MTczOTUzNDI3Mi4yLjEuMTczOTUzNDMwMS4wLjAuMA..#editorial-team